PEMBERONTAKAN PRRI SUMATERA SELATAN TANPA DEWAN GARUDA - Apriansyah, Diki Tri; Wargadalem, Farida Ratu (Sejarah dan Budaya: Jurnal Sejarah, Budaya, dan Pengajarannya, 2020)
Abstract: PRRI South Sumatra is part of the central PRRI. Initially, Barlian (Garuda Council) along with other leaders in Sumatra played a crucial role in demanding the central government to pay more attention to the regions. However, Barlian withdrew in the midst of its development, when it changed to insistence on the central government, until it become a PRRI rebellion. Under the leadership of Nawawi, PRRI South Sumatra rebellion extended until Bengkulu and MUBA. The purpose of this paper is to define how Barlian's attitude shifted to "neutral", and explain the PRRI rebellion process in South Sumatra. The methodology used was history, which consists of heuristic, data verification, interpretation, and writing. The results showed that Barlian's stance of choosing a peaceful path has resulted in his rejection of the form of violence taken by PRRI. PRRI in the South Sumatra region was part of the central PRRI rebellion under the leadership of Nawawi, with areas of struggle extending as far as Bengkulu and MUBA. The PRRI South Sumatra rebellion was difficult to be ceased by APRI, because it was based on guerrilla warfare. The rebellion ended along with the weakening and disappearance of PRRI, and other factors.  PRRI Sumsel adalah bagian dari PRRI pusat. Pada awalnya Barlian (Dewan Garuda) mempunyai peran penting bersama pemimpin lainnya di Sumatera, dalam menuntut pemerintah pusat agar lebih memperhatikan daerah. Namun, pada perkembangannya Barlian menarik diri, ketika berubah menjadi menuntut keras kepada pusat, hingga menjadi pemberontakan PRRI. PRRI Sumsel di bawah pimpinan Nawawi memberontak hingga Bengkulu dan MUBA. Tujuan dari tulisan ini adalah untuk menjelaskan bagaimana perubahan sikap Barlian menjadi “netral”, dan bagaimana proses pemberontakan PRRI di Sumsel. Metodenya adalah sejarah, yang terdiri heuristik, verifikasi data, interpretasi, dan penulisan. Hasilnya menunjukkan penolakan Barlian atas bentuk kekerasan yang diambil oleh PRRI, karena memilih jalan damai. PRRI di wilayah Sumsel merupakan bagian dari pemberontakan PRRI pusat di bawah pimpinan Nawawi, dengan wilayah perjuangan hingga Bengkulu dan MUBA. Pemberontakan PRRI Sumsel sulit diakhiri oleh APRI, karena berbasis perang gerilya. Pemberontakan berakhir seiring dengan lemah dan lenyapnya PRRI, dan faktor lainnya.